Bivariate causality between exchange rates and stock prices in Malaysia - Mohd Fahmi Ghazali; Wahi Ismail; Mohd Rushdan Yasoa’; Nelson Lajuni (The Institute for Business and Finance Research, 2008)
The main purpose of this paper is to examine the relationship between stock prices and exchange rates in Malaysia. This research considers high-frequency data of USD-MYR exchange rates and Kuala Lumpur Composite Index (KLSE) from July 22, 2005 to March 23, 2007, which is the period when the MYR was unpegged. The Johansen cointegration method suggests that there is no long-run equilibrium relationship between these two financial variables. Both Engle Granger and Toda-Yamamoto causality tests find that there is uni-directional causality running from stock prices to exchange rates.